Selexipag Treatment for Pulmonary Arterial Hypertension : A Literature Review - Hamidah, Niswah; Yuliati, Amik (Journal of Diverse Medical Research: Medicosphere, 2024)
Background. To review the current evidence regarding the use of selexipag in the treatment of PAH, evaluating its effectiveness and safety. Methods. Literature  searching  was  conducted  by collecting data through databases  such  as  PubMed, Google  Scholar, and ScienceDirect using search terms included "pulmonary arterial hypertension," and "selexipag.". Discussion. It is necessary to look at the relationship between abnormalities in PAH patients and how Selexipag itself works and to look at the side effects that occur in the research that has been carried out. Conclusion. Giving selexipag is a good method because it is effective in treating PAH patients even with comorbid diseases or connective tissue diseases. However, not much is known about the use of selexipag and the results of research on selxipag can be said to be still limited. This review highlights the ability of selexipag to improve comfort and effectiveness in the treatment of PAH patients. Keywords. Pulmonary Arterial Hypertension, Selexipag